Refractive correction in patients with heterophoria. Case reports - Legna Garrido López; Yanelis Maimó Gallego (Universidad de Ciencias Médicas de La Habana, 2022)
Introduction: Heterophoria is the misalignment of the ocular axes, which is compensated during binocular fixation using the fusion mechanism. It has a high prevalence in the population. Objective: To demonstrate the importance of a personalized optical correction in patients with heterophorias. Cases report: Four cases who attended an ophthalmology consultation for refraction due to asthenopic symptoms are presented. After a complete evaluation of every one of the cases, the presence of heterophoria was found in all of them. The existence of exophoria, mainly associated with insufficient convergence, was determined in three of them; and convergence excess esophoria was identified in one case. Personalized optical correction was indicated in all cases, taking into account the results of the examinations; also, the discomfort in the patients was eliminated. Conclusions: Heterophorias are a frequent cause of asthenopic symptoms. It is necessary to carry out an adequate study before indicating a refractive correction, considering the identification and quantification of phoria, evaluation of fusional vergences, the study of the near point of convergence, and the accommodation-convergence relationship.